Providers' Views on a Community-Wide Patient Navigation Program: Implications for Dissemination and Future Implementation. Issue 3 (May 2016) - de la Riva, Erika E.; Hajjar, Nadia; Tom, Laura S.; Phillips, Sara; Dong, XinQi; Simon, Melissa A.
The DuPage Patient Navigation Collaborative (DPNC) adapted and scaled the Patient Navigation Research Program's intervention model to navigate uninsured suburban DuPage County women with an abnormal breast or cervical cancer screening result. Recent findings reveal the effectiveness of the DPNC in addressing patient risk factors for delayed follow-up, but gaps remain as patient measures may not adequately capture navigator impact. Using semistructured interviews with 19 DPNC providers (representing the county health department, clinics, advocacy organizations, and academic partners), this study explores the critical roles of the DPNC in strengthening community partnerships and enhancing clinical services. Findings from these provider interviews revealed that a wide range of resources existed within DuPage but were often underused. Providers indicated that the DPNC was instrumental in fostering community partnerships and that navigators enhanced the referral processes, communications, and service delivery among clinical teams. Providers also recommended expanding navigation to mental health, women's health, and for a variety of chronic conditions. Considering that many in the United States have recently gained access to the health care system, clinical teams might benefit by incorporating navigators who serve a dual working purpose embedded in the community and clinics to enhance the service delivery for vulnerable populations.